Mutagenesis Induced Improvement of Coenzyme Q10 Production by Agrobacterium tumefaciens - Singh, Brajeshwar; Akhter, Yasmin (Journal for Research in Applied Sciences and Biotechnology, 2022)
Mutagenesis induced improvement of coenzyme Q10 production by Agrobacterium tumefaciens with the view of increasing CoQ10 production via strain development by UV and EMS mutagenesis is of great importance. Further optimisation of fermentation parameters such as pH, temperature, and inoculum load was done to maximise CoQ10 yield. Soil and gall samples were collected from vegetable field of Research farm located at Chatha, Jammu. Repeated isolations and purification resulted in 05 Agrobacterium tumefaciens cultures from soil samples and 07 from that of gall samples. Identification of cultures was confirmed by morphological studies. Agrobacterium tumefaciens cultures were grown on selective media to screen CoQ10 producing strains. G12 was best amongst 12 isolates; it produced 2.36 mg/g DCW. Mutagenesis using UV and EMS treatment was done to obtain a high-CoQ10-producing strain from the native isolate (G12). When exposed for 7 minutes to mutagenic UV radiation from a distance of 10 cm, the native strain (G12) showed reduction in number of colonies. Also the viability of cells was reduced when they were treated with 80 μM EMS for 30 min but it was less effective than UV mutagenesis. G12 UV mutant strain was selected after screening and tested for CoQ10 production potential by flask culturing. Our results indicate that CoQ10 content increased from 2.36 mg/g DCW to 4.34 mg/ g DCW after mutagenesis, indicating positive mutations. G12 UV mutant was further studied in batch cultures with different inoculum loads at various temperatures and range of pH, to maximize CoQ10 production along with constant fermentation parameters like agitation (180 rpm) and incubation time (96 hours). Therefore, this study suggests that amongst the culture conditions tested so far for CoQ10 production, G12 mutant strain showed maximum CoQ10 content when 108 CFU/ml of inoculum load is used at 32°C and pH 7.0.